2015
DOI: 10.1186/s12879-015-1295-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of human papillomavirus vaccination in South Africa accounting for human immunodeficiency virus prevalence

Abstract: BackgroundThis study aims at evaluating the cost-effectiveness of a 2-dose schedule human papillomavirus (HPV) vaccination programme of HPV and human immunodeficiency virus (HIV) naïve 12-year-old girls, in addition to cervical cancer (CC) screening alone, in South Africa. The study aims to account for both the impact of the vaccine among girls who are HIV-positive (HIV+) as well as HIV-negative (HIV-) population.MethodsA previously published Markov cohort model was adapted to assess the impact and cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…The randomised trials on cervical cancer screening have all been conducted in India, and have documented the efficacy of visual inspection, cytology screening and HPV-screening [1821]. Numerous epidemiological studies have consistently documented that in countries where the resources exist to ensure high-quality and good coverage of the population, cytology screening contributes to decreasing the incidence of advanced-stage cancers and mortality associated with cervical cancer [2224].…”
Section: Secondary Cervical Cancer Prevention: Cervical Cancer Screeningmentioning
confidence: 99%
“…The randomised trials on cervical cancer screening have all been conducted in India, and have documented the efficacy of visual inspection, cytology screening and HPV-screening [1821]. Numerous epidemiological studies have consistently documented that in countries where the resources exist to ensure high-quality and good coverage of the population, cytology screening contributes to decreasing the incidence of advanced-stage cancers and mortality associated with cervical cancer [2224].…”
Section: Secondary Cervical Cancer Prevention: Cervical Cancer Screeningmentioning
confidence: 99%
“…The randomized trial studies done in different places on cervical cancer screening have shown the efficacy of visual inspection, cytology screening and HPV screening [22][23][24]. Many studies have acknowledged that in countries where the resources exist to confirm high value and good coverage of the people, cytology screening provides to decreasing the incidence of advanced stage cancers and death related with cervical cancer [25][26][27].…”
Section: Secondary Prevention Of Cervical Cancermentioning
confidence: 99%
“…In 2014 only 58 countries had incorporated HPV vaccination into national immunization campaigns and mostly in high-income settings [27]. More recently, countries in SSA have begun to implement HPV vaccination nationwide with support from global health programs [29], which may have significant cost efficacy [30]. Unfortunately, the details of real-world vaccination uptake in HIV-infected girls and women remain difficult to accomplish [31].…”
Section: Cervical Cancermentioning
confidence: 99%